2‐Methoxystypandrone inhibits signal transducer and activator of transcription 3 and nuclear factor‐κB signaling by inhibiting Janus kinase 2 and IκB kinase. Issue 4 (3rd March 2014) - Kuang, Shan; Qi, Chunting; Liu, Jiawei; Sun, Xiaoxiao; Zhang, Qing; Sima, Zhenhua; Liu, Jingli; Li, Wuguo; Yu, Qiang
<x xml:space="preserve">Abstract</x> Constitutive activation of the signal transducer and activator of transcription 3 (STAT3) or the nuclear factor‐κB (NF‐κB) pathway occurs frequently in cancer cells and contributes to oncogenesis. The activation of Janus kinase 2 (JAK2) and IκB kinase (IKK) are key events in STAT3 and NF‐κB signaling, respectively. We have identified 2‐methoxystypandrone (2‐MS) from a traditional Chinese medicinal herb Polygonum cuspidatum as a novel dual inhibitor of JAK2 and IKK. 2‐MS inhibits both interleukin‐6‐induced and constitutively‐activated STAT3, as well as tumor necrosis factor‐α‐induced NF‐κB activation. 2‐MS specifically inhibits JAK and IKKβ kinase activities but has little effect on activities of other kinases tested. The inhibitory effects of 2‐MS on STAT3 and NF‐κB signaling can be eliminated by DTT or glutathione and can last for 4 h after a pulse treatment. Furthermore, 2‐MS inhibits growth and induces death of tumor cells, particularly those with constitutively‐activated STAT3 or NF‐κB signaling. We propose that the natural compound 2‐MS, as a potent dual inhibitor of STAT3 and NF‐κB pathways, is a promising anticancer drug candidate.